CORRESPONDENCE ANALYSIS OF FRUIT AND VEGETABLE WASTE AMONG CONSUMERS IN VOJVODINA - Ubiparip Samek, Dragana (Food and Feed Research, 2022)
Fresh fruit and vegetables contribute to almost 50% of food wasted by households in the EU. To understand the main reasons for wasteful behaviour among the consumers in Vojvodina (Serbia) cross-sectional data were collected through a self-administrated online survey of 711 correspondents. The questions presented in the study focused on the method of preserving the fruits and vegetables in domestic conditions before their consumption. Self-estimation of wasteful behaviour in the household and socio-demographic factors, including the respondents' self-estimated health status, were analysed using the correspondence analysis. The results showed that the first two dimensions explained for 95.06% of the total per cent of inertia (statistically significant at p
Keywords: fruit waste; vegetable waste; fruit storage; vegetable storage; wasteful behaviour